Dialoog met die self: die labirint as medium van intrapersoonlike kommuikasie - Roodt, Zarine (Department of Communication Science, University of the Free State, 2009)
This article aims at investigating labyrinth walking as a form of communication with the self. Based primarily on the concept of self-talk as a distinguishable form of communication, the author draws a number of conclusions, mainly in relation to the concepts of listening and meaning. It is inferred that the labyrinth is a communication medium and that the labyrinth walker as source / receiver is afforded the opportunity to embrace silence, and to enter into dialogue with the self in the heart of the labyrinth in order to find meaning in both the personal and transpersonal context. It could be concluded that the labyrinth is a medium of intrapersonal communication, with the physical activity of walking the labyrinth a visual manifestation of the process of intrapersonal communication, and the circuitous process through which we gain access to our innermost communicative and communicating self.
Keywords: Labyrinth walking; Self-talk; Intrapersonal communication